THE IMAGE OF ISLAMIC HIGHER EDUCATION REVIEWED FROM PROMOTIONS AND TUITION FEES AS WELL AS ITS IMPLICATIONS FOR COLLEGE DECISIONS - Sarmigi, Elex; Mahabbati, Suci; Tila, Marda (Institut Agama Islam Negeri Kerinci, 2025)
This research was conducted to determine how interested parents of high school students in Kerinci Regency and Sungai Penuh City are in choosing an Islamic college for their children's further studies. The factors tested in this research are the image of Islamic universities, promotions, and tuition fees. The sample for this research was 227 respondents. Data was collected using a questionnaire. Data analysis uses the Structural Equation Model (SEM) approach with the help of the SmartPLS 2.3.9 application. The results of this research show that promotions and tuition fees have a positive and significant effect on the image of Islamic universities and influence the interest of students' parents in recommending Islamic universities to their children to continue their studies. The image of Islamic higher education mediates the relationship between promotion and tuition fees in the Decision to choose an Islamic higher education institution. The type of mediation effect is partial mediation.